2017
DOI: 10.1111/scs.12421
|View full text |Cite
|
Sign up to set email alerts
|

Why do some older adults start drinking excessively late in life? Results from an Interpretative Phenomenological Study

Abstract: Introduction This is a pioneering qualitative phenomenological hermeneutical study investigating a so far under‐investigated group of older adults with very late‐onset alcohol use disorder. The number of older adults is increasing, and the number of older adults with alcohol problems is increasing accordingly. We investigated older adults with very late‐onset alcohol use disorder to identify what causes some people to develop problems with alcohol after the age of 60. Method We interviewed 12 Danish individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 41 publications
7
32
0
Order By: Relevance
“…However, population aging is concurring to a higher number of older adults with alcohol problems, which reinforce the importance of studying demographic trends of alcohol use and alcohol use problems in this specific population. One of the few existent studies demonstrated that alcohol use, binge alcohol use, and alcohol use disorders increased among older adults, particularly in females, and among older adults with multiple chronic conditions (Han et al, 2017); another study conducted with a sample of older adults with very late-onset alcohol use disorder found that using alcohol as a coping strategy was one of its main associated factors (Emiliussen et al, 2017). Moreover, older persons have unique risks with alcohol consumption, and special vulnerabilities to the effects of moodaltering substances.…”
Section: Discussionmentioning
confidence: 99%
“…However, population aging is concurring to a higher number of older adults with alcohol problems, which reinforce the importance of studying demographic trends of alcohol use and alcohol use problems in this specific population. One of the few existent studies demonstrated that alcohol use, binge alcohol use, and alcohol use disorders increased among older adults, particularly in females, and among older adults with multiple chronic conditions (Han et al, 2017); another study conducted with a sample of older adults with very late-onset alcohol use disorder found that using alcohol as a coping strategy was one of its main associated factors (Emiliussen et al, 2017). Moreover, older persons have unique risks with alcohol consumption, and special vulnerabilities to the effects of moodaltering substances.…”
Section: Discussionmentioning
confidence: 99%
“…IPA has been used within the AUD and alcohol addiction field (see e.g. Emiliussen, Andersen & Nielsen, 2017;Shinebourne & Smith 2009, Toye, Williamson, Williams, Fairbank & Lamb, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy episodic drinking at least once a week is 60 g of pure alcohol or five or more drinks on one occasion) is reported by over one fifth of Europeans aged 15 years and over (WHO, 2014b). Although alcohol use declines with age (Grundstrom, et al, 2012), studies have shown that alcohol consumption is higher in older adult population (León-Munoz, et al, 2015;Emiliussen, et al, 2017). WHO (2014a) states that alcohol consumption is generally more frequent in older people than in other age groups.…”
Section: Epidemiology Of Alcohol Dependencementioning
confidence: 99%